Heat exchanger equipment field manual : common operating problems and practical solutions - Stewart, Maurice (Gulf Professional Pub., 2013)
From upstream to downstream, Heat Exchangers are utilized in every stage of the petroleum value stream. An integral piece of equipment, heat exchangers are among the most confusing and problematic pieces of equipment in the petroleum processing operations. This is especially true for engineers just entering the field or seasoned engineers that must keep up with the latest methods for in-shop and in-service inspection, repair, alteration and re-rating of equipment. Heat Exchanger Equipment Field Manual provides engineers and operators with an easy to understand working manual to the recent developments in heat exchanger technology and in the diagnosis and correction of operating problems. The objective of this book is to provide the reader with sufficient information to make better logical choices in designing and operating the system. Heat Exchanger Equipment Field Manual provides an indispensable means for the determination of possible failures and for the recognition of the optimization potential of the respective heat exchanger. Step-by-step procedure on how to design, perform in-shop and in-field inspections and repairs, perform alterations and re-rate equipment Select the correct heat transfer equipment for a particular applicationApply heat transfer principles to design, select and specify heat transfer equipmentEvaluate the performance of heat transfer equipment and recommend solutions to problemsControl schemes for typical heat transfer equipment application.
Includes index.
Keywords: Heat exchangers -- Maintenance and repair.; elektronické knihy; electronic books